Coffee consumption and risk of first and recurrent venous thromboembolism (VTE) and all-cause mortality after VTE - Bechstein, Sara (UiT Norges arktiske universitet, 2017)
Coffee is one of the most consumed beverages in the world and it has been reported to be associated with the risk of cardiovascular disease. Venous Thromboembolism (VTE) is a major public health burden, although its association to dietary habits including coffee consumption is still underinvestigated. The aim of this thesis was to investigate the association between daily coffee intake and the risk of incident VTE, as well as recurrence and all-cause mortality after a first VTE event. The study included 30,236 participants aged 25-97 from the fourth (1994-95), fifth (2001-02) and sixth (2007-08) surveys of the Tromsø study. Information about daily coffee consumption was obtained from questionnaires at the time of enrollment and updated at each of the subsequent surveys. All cases of incident VTE, recurrent VTE and death were registered during the follow-up period (end of follow up: 31st Dec 2012). A total of 491 incident VTEs occurred during 312,688 person-years (overall IR 1.57, 95% CI 1.44-1.72). Consuming at least one cup of coffee per day was inversely associated with the risk of incident VTE (hazard ratio (HR) 0.63, 95% CI 0.44-0.89) and the risk estimates were particularly strong for moderate coffee consumers (3-4 cups: HR 0.58, 95% CI 0.39-0.84, 5-6 cups: HR 0.59, 95% CI 0.4-0.88) compared to coffee abstainers. Among 491 VTE cases, 76 experienced recurrent VTE (recurrent rate: 35.0, 95% CI 28.0-43.8) and 240 died (mortality rate: 99.1 95% CI, 79.4-115.8) during the mean follow-up of 4.9 years. Coffee drinking was associated with a 66% reduced risk of recurrence (HR 0.34, 95% CI 0.17-0.67) and 18 % lower risk of death (HR 0.82, 95% CI 0.50-1.34). The inverse association persisted for all coffee consumption categories. In conclusion, coffee drinking was inversely associated with the risk of incident VTE, recurrence and death. A possible U-shape association was revealed, indicating that moderate coffee intake might reduce the risk of VTE, recurrence event and death. However, further epidemiological studies ...